A mixed methods evaluation of the usability of Feel Your Best Self - Iovino, Emily A.; Chafouleas, Sandra M.; Torres, Rabbecca C.; Weiner, Michael A. (Frontiers in Education, 2024)
Feel Your Best Self (FYBS) is an online toolkit developed to facilitate teaching emotion-focused coping skills to elementary-aged children. This study presents findings from a mixed methods evaluation of FYBS usability. Survey participants (n = 29) and interview participants (n = 12) shared their perceptions of FYBS, including strengths and areas for growth along with adaptations made relevant to their unique contexts. Results indicated that participants found FYBS to be highly usable, and that both children and implementers responded well to FYBS. FYBS was easy to use, and implementers were able to personalize materials and indicated a desire for additional features to enhance usability. Findings provide considerations for the iteration of FYBS materials along with directions for features to explore in future research.